What is the first step to solving this equation? -5c + 6 = -4
2 answers:
Answer:
subtract 6 from both sides.
-5c = -10
then divide both sides by -5 (negative divided by a negative is a positive)
c = 2
Step-by-step explanation:
Step-by-step explanation:
Hey, there!!
The given equation is : -5c + 6 = -4
The first step olis to take (+6) in right side,
![- 5c = - 4 - 6](https://tex.z-dn.net/?f=%20-%205c%20%3D%20%20-%204%20-%206)
now, another step is add ( -4 and -6)
![- 5c = - 10](https://tex.z-dn.net/?f=%20-%205c%20%3D%20%20-%2010)
Now, divide -10 by -5.
![c = \frac{ - 10}{ - 5}](https://tex.z-dn.net/?f=c%20%3D%20%20%20%5Cfrac%7B%20-%2010%7D%7B%20-%205%7D%20)
Therefore, c= 2.
<em><u>Hope it helps</u></em><em><u>.</u></em><em><u>.</u></em>
You might be interested in
Answer: Well if i am correct she would be cutting acute angles.
Answer:
½
Step-by-step explanation:
we know y=mx+h
y= ½ x + 6 so m=½
Answer:
Step-by-step explanation:
3.48/24= 14.54 cents/ oz
6.49/48= 13.52 cents/oz
School is dumb....................................
the answer for this question is p=5/3 ,(q)=3/2